Online Booking System for Chalet Sri Nelayan - Roslan, Nuratira Murni; Mohd Salikon, Mohd Zaki (Applied Information Technology And Computer Science, 2022)
The Online Booking System is a system which goes about as another booking strategy for Chalet Sri Nelayan. The reason for fostering this system is to execute the new Online Booking System of Chalet Sri Nelayan contrasted with the past manual booking process as far as execution, dependability, and effectiveness. This system acknowledges the enrollment of the guests to book the room at Chalet Sri Nelayan. To guarantee the advantages of the system goes just to the guests, they should enroll to see the subtleties of the room data. With this system, guests will actually want to check the accessible space for reservation and the subtleties of the room. Besides, guests can straightforwardly hold the accessible room on the system. This system will burn-through less time contrasted with the past manual system and this system is extremely productive to save booking subtleties as opposed to saving it on a PC.